2019
DOI: 10.1177/1756287219875576
|View full text |Cite
|
Sign up to set email alerts
|

Oct-4: a prognostic biomarker of urinary bladder cancer in North India

Abstract: Background: The objective of this study was to evaluate Octamer-binding transcription factor 4 (Oct-4), neutrophil to lymphocyte ratio (NLR) and body mass index (BMI) as independent prognostic biomarkers for prediction of urinary bladder cancer (UBC) outcomes. With the advancement in prognostic biomarker discovery, tumor recurrence is difficult to accurately predict in UBC. UBC is costly to treat due to the requirement of frequent invasive follow-up sessions. Therefore, it is of utmost importance to evaluate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our results showed an absence of modulation of the expression of the stem cell marker OCT4 in adjacent non-tumor tissue, but did show OCT4 expression in tumor tissue consistent with other authors, who have reported OCT4 protein expression in various human cancer tissues such as stomach [9], pancreas [11], bladder [13], ovary [14], prostate [15], and CRC, but not in normal somatic tissues [38]. It is believed, then, that OCT4 reactivation occurs in cells that have undergone malignancy [30], in which the expression of pluripotency genes by stem cells has been related to tumor proliferation, metastasis, and poor prognosis [10].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed an absence of modulation of the expression of the stem cell marker OCT4 in adjacent non-tumor tissue, but did show OCT4 expression in tumor tissue consistent with other authors, who have reported OCT4 protein expression in various human cancer tissues such as stomach [9], pancreas [11], bladder [13], ovary [14], prostate [15], and CRC, but not in normal somatic tissues [38]. It is believed, then, that OCT4 reactivation occurs in cells that have undergone malignancy [30], in which the expression of pluripotency genes by stem cells has been related to tumor proliferation, metastasis, and poor prognosis [10].…”
Section: Discussionsupporting
confidence: 92%
“…Among the transcription factors described as regulators of pluripotency and maintenance of CSCs is the octamer-binding protein 4 (OCT4; also known as POU domain, class 5, transcription factor 1 (POU5F1)), an oncofetal protein that promotes self-renewal and maintenance of pluripotency of embryonic stem cells and induced stem cells, and which has been found to be involved in the progression and poor prognosis of various cancers [7], including gastric [8][9][10], pancreatic [11], breast [12], bladder [13], ovarian [14], prostate [15], and hepatocellular carcinoma [16]. However, few studies have included OCT4 evaluation in RC [17,18], and even fewer have evaluated its clinical significance in these patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…Higher OCT4 expression in BC was shown to be linked with the higher grade of human BC and its recurrence after surgery [56]. Moreover, a recent study on 39 BC tissue samples in India revealed that OCT4 expression was correlated with gender, tumor grade, tumor stage, lymph node status, recurrence, progression, and treatment modality [57]. These data indicate that OCT4 could be a valuable clinical diagnostic and prognostic marker for the progression of BC and may become an attractive therapeutic target to establish new therapies for urothelial carcinoma.…”
Section: Role Of Oct4mentioning
confidence: 99%